Oxidative Stress and Inflammatory Biomarkers as Predictors of Cardiovascular Complications in Type 2 Diabetes Mellitus: A Clinical and Biochemical Evaluation - Muhammad Hussain, Nasir Siddique, Abdur Rauf Hammad, Amir Jalal, M. Shakil Zari Khawri Siddiqui, Waqas Qurshi, Muhammad Nasir Shahbaz, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Cardiovascular disease (CVD) is a major cause of morbidity and mortality among individuals with Type 2 Diabetes Mellitus (T2DM). Oxidative stress and systemic inflammation are key mechanisms contributing to vascular dysfunction and cardiac complications. This study evaluates the predictive value of oxidative and inflammatory biomarkers in identifying cardiovascular risk among T2DM patients. Methods: A cross-sectional study was conducted at Abwa Medical College, Faisalabad, and the University of Lahore Teaching Hospital, Lahore Pakistan, from March 2022 to May 2023. A total of 130 T2DM patients were enrolled and categorized into two groups: those with cardiovascular complications (n = 62) and those without (n = 68). Clinical data, biochemical parameters, oxidative stress markers malondialdehyde (MDA) and superoxide dismutase (SOD) and inflammatory biomarkers (hs-CRP, IL-6, TNF-α) were analyzed. Echocardiography and carotid intima-media thickness (CIMT) assessments were performed. Statistical analysis included t-tests, correlation analysis, and logistic regression. Results: Patients with cardiovascular complications exhibited significantly higher MDA levels (p < 0.001), lower SOD activity (p = 0.001), and elevated inflammatory biomarkers including hs-CRP, IL-6, and TNF-α (p < 0.001). Echocardiographic findings revealed reduced ejection fraction and increased left ventricular mass index in the cardiovascular group (p < 0.001). MDA showed strong positive correlation with CIMT, while SOD demonstrated a significant negative correlation. Logistic regression identified elevated MDA, low SOD, high hs-CRP, and elevated IL-6 as independent predictors of cardiovascular complications in T2DM. Conclusion: Oxidative stress and inflammatory biomarkers are strong predictors of cardiovascular complications in T2DM. Elevated MDA, reduced SOD activity, and increased hs-CRP and IL-6 correlate with structural and functional cardiac abnormalities. Integrating these biomarkers into clinical evaluation may enhance early cardiovascular risk detection and guide preventive strategies for diabetic patients. Keywords: Type 2 diabetes mellitus, oxidative stress, inflammation, cardiovascular disease, MDA, SOD, hs-CRP, IL-6, TNF-α.